Electricity marginal cost pricing : applications in eliciting demand responses - Greer, Monica (Elsevier, 2012)
Packed with case studies and practical real-world examples, Electricity Marginal Cost Pricing Principles allows regulators, engineers and energy economists to choose the pricing model that best fits their individual market. Written by an author with 13 years of practical experience, the book begins with a clear and rigorous explanation of the theory of efficient pricing and how it impacts investor-owned, publicly-owned, and cooperatively-owned utilities using tried and true methods such as multiple-output, functional form, and multiproduct cost models. The author then moves on to include self-contained chapters on applying estimating cost models, including a cubic cost specification and policy implications while supplying actual data and examples to allow regulators, energy economists, and engineers to get "a feel" for the methods with which efficient prices are derived in today's challenging electricity market. The book is accompanied by a companion website which will allow for the testing of methods and validating results. A guide to cost issues surrounding the generation, transmission, and distribution of electricity Clearly explains cost models which can yield the marginal cost of supplying electricity to end-users Real-world examples that are practical, meaningful, and easy to understand Explans the policy implications of each example Provide suggestions to aid in the formation of the optimal market price